ANALISIS KONTRIBUSI PENDAPATAN USAHA KOPRA TERHADAP KEBUTUHAN HIDUP LAYAK (KHL) DI DESA POLEWALI KECAMATAN BAMBALAMOTU KABUPATEN MAMUJU UTARA PROVINSI SULAWESI BARAT - Saharia Kassa, Rukavina Baksh, Ahmad Mukhlisin, (AGROTEKBIS, 2016)
This research aims to know the magnitude of the average income of the copra entrepreneurs and the magnitude of the income contribution of the copra entrepreneur to the KHL. This research was carried out in the village of Polewali, Bambalamotu subdistrict, Regency of North Mamuju, West Sulawesi province in December 2015. The respondents determination is done by a simple random sampling method, determining in the number of samples is done using the formula of slovin, respondents were taken in this research as much as 31 KK of 74 KK population numbers. This research is carried out by surveys, data collected in the form of primary and secondary data. The results of the analysis showed that the income earned of copra entrepreneur in the village of Polewali is Rp. 10.561.780/four months and it is when averaged is Rp. 2.640.445/month. The results of the analysis of contribution rate of necessities of worthy life (MOE) showed that the necessities of worthy life which have met the criteria based on Sinukaban is of 1.04 percent, the WORLD BANKS US 1 is 1,58%, and BPS is 1.05% whereas based on the criteria of the WORLD BANKS US 2 is 0.79%, and on the basis of 0.33% KHl and UMP West Sulawesi province is 0.37% so the revenue contribution by employers in the village of Polewali copra is not fully met the criteria of the necessities of worthy life of 1%.